Strengthening School Literature Movement in Elementary School During the Covid-19 Pandemic - Nurul Istiq'faroh; Wahyu Maulida Lestari; Arie Widya Murni; Evi Mahsunah; Amiruddin Hadi Wibowo (STAI Hubbulwathan Duri, 2022)
Literacy development in Indonesia is still reported to be low. This is written in the findings of a 2020 program for international student assessment (PISA) survey, which found that Indonesia ranked 72 out of 79 countries in the world in reading literacy. During the Covid-19 pandemic, the implementation of the school literacy movement program was done online. The purpose of this study is to investigate the implementation of SLM throughout the Covid-19 era, as well as the barriers encountered by teachers during the SLM implementation process. The case study method is used in this work, which takes a qualitative approach. Data was collected by observation, interviews, and documentation, and data was analyzed utilizing triangulation techniques in three stages: collection, reduction, and conclusion. The findings revealed that schools were still practicing the three steps of SLM, namely habituation, development, and learning. During the epidemic, literacy exercises are introduced in which students are directed to be productive in their work through writing tasks. The work of the students is published in the form of a book. The challenge to implement SLM during the Covid-19 pandemic has been teachers' inability to manage students' reading comprehension exercises properly.